The Influence of Work Motivation and Work Environment on Job Satisfaction and Employee Performance During the Covid-19 Pandemic - Dwi Yuli Anugrah; Sumardi Lasise; Andi Nur Baumassepe (Magister Management, Hasanuddin University, 2022)
The Covid-19 pandemic that occurred at the beginning of 2020 has brought enormous changes to human life in the world, including in Indonesia. The impact is felt not only in one sector but in almost all sectors of life, including the banking sector. Bank BNI Makassar Regional Office is one of the companies that continue to operate with the WFO (Work from Office) work system amid the rise of the Covid-19 Virus. The purpose of this study was to analyze the effect of work motivation and work environment on job satisfaction and employee performance at Bank BNI Makassar Regional Office during the Covid-19 pandemic. The sample is 105 permanent employees. Data was collected by means of questionnaires and interviews. Data were analyzed using Path Analysis. The results showed that work motivation, work environment, and job satisfaction had a direct, positive, and significant effect on performance. Likewise, work motivation and work environment have a direct, positive, and significant effect on job satisfaction. Job satisfaction is able to mediate the relationship between work motivation and work environment on employee performance during the Covid-19 pandemic.